Molecular Dynamics Simulation of Nanomachining Mechanism between Monocrystalline and Polycrystalline Silicon Carbide. Issue 8 (3rd July 2021) - Liu, Bing; Yang, Haijie; Xu, Zongwei; Wang, Dongai; Ji, Hongwei
Abstract: As an advanced ceramics material, silicon carbide (SiC) is extensively applied in numerous industries. In this study, molecular dynamics method is used to comparatively investigate the nanomachining mechanism between monocrystalline SiC (mono‐SiC) and polycrystalline SiC (poly‐SiC) ceramics. Four simulations are performed for the two materials with and without ultrasonic vibration‐assisted machining (UVAM). The diamond tool is set as a non‐rigid body and vibrated along the depth direction with 100 GHz in frequency and 0.5 nm in amplitude. The effects of material and ultrasonic vibration on the nanomachining mechanism of SiC are analyzed in depth, including the surface generation, subsurface damage, and tool wear. It is determined that the machinability of SiC ceramics can be effectively improved by UVAM. The machining‐induced damage extent of poly‐SiC is more serious than that of mono‐SiC. It is also found that UVAM can effectively reduce the machining‐induced damage, decrease the machining resistance, and increase the possibility of ductile removal, but bring about a slightly larger tool wear. Abstract : Molecular dynamics simulation is used to comparatively investigate the nanomachining mechanism between monocrystalline and polycrystalline silicon carbide (SiC). Four groups of simulations are performed on the two materials with and without ultrasonic vibration‐assisted machining. The effects of material and ultrasonic vibration on the nanomachining mechanism of SiC are analyzed, including the material removal behavior, subsurface damage and tool wear.